SBA‐15 modified by incorporation of alkali metals: Effect of Its structural changes on the catalytic properties of Fe/SBA‐15 system in the Fischer–tropsch synthesis - Cano, Leonardo Andres (2020)
A mesoporous SBA‐15 solid is doped with Li, K, or Cs. These systems are used as support of iron nanoparticles, and each composite is utilized as a catalyst in the Fischer-Tropsch synthesis. After the activation treatment, the same Fe species are detected in all solids: Fe3O4, α‐Fe, and Fe2+ inside SBA‐15 walls. However, the species percentages and their distribution are different according to the dopant present. In all "working" catalysts, a mixture of carbides ε´‐Fe2.2C and χ‐Fe2C5, Fe3O4, and ions Fe+2 inside the SBA‐15 walls are found. Alkali cations produce different amounts and strengths of basic sites. At 1 atm and T  = 703 K, the catalytic activity order is: Li > K > no doped > Cs, and the alkali metals favor the production of olefins. At 20 atm, the activity is considerably higher, even at a temperature as low as 543 K, which is attributed to structural properties of the support and to diffusional effects. All catalysts show a promising hydrocarbon production in the gasoline range. The influence of alkali metals is discussed in terms of electrostatic effects, and the limited hydrocarbon chain growth is attributed to the control over size of active iron species.